Ageing in Australia : Challenges and Opportunities - O'Loughlin, Kate; Browning, Colette; Kendig, Hal (Springer New York : Imprint: Springer, 2017)
This stimulating volume examines the many faces of Australia's ageing population, the social and health issues they contend with, and the steps being taken-and many that should be taken-to help ensure a more positive and productive later life. Individual and societal ageing are conceptualized as developmental in nature, socially diverse, and marked by daily life challenges stemming from the country's economic structures, attitudes, geography, political landscape, and infrastructure. Wide-ranging coverage (e.g., health, inequalities, employment, transportation) assesses options available to older people, and the role of families, employers, service providers, government agencies, and others in promoting or expanding those choices. The book's double emphasis on challenges in older people's lives and opportunities for enhancing their quality of life is on clear display as case studies examine policy issues-and propose solutions-in a societal and individual context. Included in the coverage: · Australian developments in ageing: issues and history · Cultural diversity, health, and ageing · Indigenous Australians and ageing: responding to diversity in policy and practice · Enhancing the health and employment participation of older workers · Housing and the environments of ageing · Health services and care for older people The rich examples in Ageing in Australia contain a depth of understanding and evidence for sociologists, gerontologists and psychologists studying ageing, health care professionals providing care to older people, and policy analysts assessing areas for improvement. .
Keywords: Social sciences.; Public health.; Medical research.; Social policy.; Aging.; Quality of life.; Health psychology.; elektronické knihy; electronic books